Pengaruh Penggunaan Media Story Cube Berbasis Teks Narasi terhadap Membaca Pemahaman Siswa Kelas IV SDN 24 Cakranegara - Ida Andriani; Syaiful Musaddat; Syarifuddin (Mataram University, 2026)
Reading comprehension is one of the fundamental skills that elementary school students need to master, particularly in the fourth grade, as it plays a crucial role in understanding narrative texts. This study was motivated by the low reading comprehension ability of fourth-grade students at SDN 24 Cakranegara in comprehending narrative texts, as indicated by preliminary observations and an initial test with an average score of 63, as well as the use of conventional teaching methods with limited implementation of innovative learning media. This study aimed to determine the effect of using story cube media based on narrative texts on the reading comprehension ability of fourth-grade students at SDN 24 Cakranegara. The study employed a quantitative approach using a pre-experimental method with a One-Group Pretest–Posttest Design. The research involved 24 students, of whom 19 with complete data were included in the final analysis. Data were collected using a validated reading comprehension test instrument, which was evaluated by two experts and obtained an average validity score of 89% (categorized as highly feasible). The collected data were analyzed using the Shapiro–Wilk normality test, followed by the Paired Sample t-test and N-Gain analysis. The hypothesis test revealed a significance value (2-tailed) of 0.000 < 0.05, indicating that the use of story cube media had a statistically significant effect on students' reading comprehension ability. This finding was supported by the increase in the mean score from 62.32 on the pretest to 75.26 on the posttest. Furthermore, the N-Gain score of 0.3295 was classified as a moderate improvement. Therefore, the null hypothesis (H₀) was rejected and the alternative hypothesis (Hₐ) was accepted, indicating that the use of narrative text-based story cube media significantly improved the reading comprehension ability of fourth-grade students at SDN 24 Cakranegara.